Studi Eksperimen Terhadap Performansi Mesin Bubut Bemato Series 44378 BU 27 Berdasarkan Penyimpangan Kesilindrisan Produk Hasil Pembubutan - Erwansyah, Erwansyah; Husman, Husman; Gentara, Raju (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Machine tools are machines used to produce products in the industrial sector. Machine tools that have been used for a very long time will naturally experience a decrease in performance, this is also experienced by the Bemato Series 44378 BU 27 lathe in Polman Negeri Babel which has entered its service life for approximately 10 years. The factors that affect the results of lathe machining are machining parameters, including cutting speed, cutting depth, and engine rotation speed. To find out how good the performance of the lathe can be done in various ways or tests, one of which is the cylindricity test. The material used in this test is st-41 steel. From the results of the research conducted, the largest deviation in cylindricity of the Bemato Series 44378 BU 27 lathe is 769 ?m. Based on the deviations that occur when compared with the Grades of tolerance table, the results are included in the IT 15 grade. This value can be concluded that the BU 27 machine has experienced a decline in performance that is very far from its minimum standard, and is only capable of producing workpieces with tolerances above 769 ?m. With this decline in performance, the lathe that was studied must be repaired and maintained immediately so that the performance of the machine can be returned to standard conditions.